Proses Kreatif Klaras Reggae band dalam mencipta lagu KAmpung Rawa - pradityatama, ega (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
The journal entitled "The Creative Process of Klaras Reggae band in creating the song Kampung Rawa" began with the author's interest that arose after watching the performance and listening to songs from Klaras Reggae. This interest arises because the music played by Klaras Reggae feels comfortable, the result of the combination of the Rock and Reggae genres. Music that attracts attention because it is different from other Reggae bands in Klaten. Klaras Reggae is a music group that has just started its career in Klaten Regency, but has managed to create its musical character. This musical character then became the identity of their creativity to this day. This study uses a qualitative method to reveal the results descriptively. The data used in this study consists of two types: primary data, which is data obtained directly from the original source, and secondary data, which is data obtained through indirect sources, such as through other people or documents. There are several studies using Rhodes' concept of the four "P's" contained in Utami Munandar in his book entitled Creativity and Talent. The values of Klaras Reggae's creativity in creating songs are analyzed by looking at elements (1) personal, (2) process, (3) driving factors (press), and (4) results. The results of this study show that Klaras Reggae has different ideas in creating the song Kampung Rawa. Through the Rocksteady genre, they want to highlight a strong musical character, which results from a mature musical concept. This musical character is the reason why Klaras Reggae always gets positive appreciation from its listeners.